Adenovirus Microsatellite Reveals Dynamics of Transmission during a Recent Epidemic of Human Adenovirus Serotype 14 Infection - Houng, Huo-Shu H. (American Society for Microbiology (ASM), 2009)
This study reveals diverse-length polymorphisms in long mononucleotide repeats (microsatellites) in several serotypes of epidemic human respiratory adenovirus. The length of one of these microsatellites, a homopolymeric thymidine [poly(T)] repeat, is measured in 68 isolates of adenovirus serotype 14. These isolates were collected during a series of sudden and sometimes fatal outbreaks among both military recruits and civilians as the virus emerged for the first time in the United States in 2006 and 2007. The results demonstrate the usefulness of adenoviral microsatellites as high-resolution molecular strain markers. The described homopolymer is hypervariable in length, varying from 12 to 17 bp in the analyzed sample set. All intermediate lengths were identified in at least one isolate. Furthermore, the specific length of the marker is stable for significant periods of time (up to 7 months) at individual sites where the virus is in consistent circulation. The microsatellite also can maintain specific length identity through site-to-site transmission events, as determined by the analysis of isolates from three advanced training sites that appeared to be subject to pathogen transfer from one of the affected recruit training installations. Public database searches revealed that the polymorphic nature of the microsatellite extends to other species B serotypes, and that other polymorphic microsatellites can be identified readily in a variety of epidemic respiratory adenovirus clades. This study shows that microsatellites are a ubiquitous source of polymorphic markers for human adenoviruses and demonstrates their use through an epidemiological analysis of isolates from a recent North American epidemic.